Exploring The Impact of Natural Elements on User Experience in Kitchen Design and Functionality - Toba, Juliana (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
This study investigates the influence of natural elements on users' experiences in kitchen spaces, focusing on aspects such as natural light, color, water features, and organic materials. Employing a quantitative survey methodology, data were collected from 80 kitchen users in the Northeast of England, specifically in Middlesbrough and Newcastle. The findings reveal a strong inclination towards the incorporation of natural elements, with 75% of respondents considering their inclusion beneficial for enhancing kitchen environments. Furthermore, a striking 90% of participants believe that such elements can significantly improve overall well-being and mood. he survey results indicate that natural light is particularly valued, with 52.5% of respondents strongly agreeing that it enhances the ambiance of kitchen spaces. Additionally, 100% of participants who had experience in kitchens featuring natural elements reported positive impacts, with 37.5% noting that these features create a friendly atmosphere. However, 60% of respondents had not previously encountered kitchens designed with natural elements, highlighting an opportunity for innovation in kitchen design. These insights underscore the importance of biophilic design principles in fostering not only aesthetic appeal but also emotional well-being among users. As the demand for healthier living environments increases, this research advocates for the integration of natural elements in kitchen spaces to enhance user experiences. Ultimately, the findings contribute to a growing body of literature on the significance of nature in interior design, offering valuable guidance for architects, interior designers, and homeowners seeking to create functional and inviting kitchen environments.